2019
DOI: 10.1074/jbc.ra119.007597
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical insights into the catalytic mechanisms of two insect chitin deacetylases of the carbohydrate esterase 4 family

Abstract: Insect chitin deacetylases (CDAs) catalyze the removal of acetyl groups from chitin and modify this polymer during its synthesis and reorganization. CDAs are essential for insect survival and therefore represent promising targets for insecticide development. However, the structural and biochemical characteristics of insect CDAs have remained elusive. Here, we report the crystal structures of two insect CDAs from the silk moth Bombyx mori : Bm CDA1, which may functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…Murine skin tissues were collected 12 days after tick repletion, and the B. burgdorferi burden was detected using qPCR. ns, non-significant; *p > .05 modes (Liu et al, 2019). Therefore, PM_CBP, which harbours a CDA- We found that interference with PM_CBP expression reduces the thickness of the Ixodes PM and impacts its integrity, thereby increasing its permeability to large molecules.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Murine skin tissues were collected 12 days after tick repletion, and the B. burgdorferi burden was detected using qPCR. ns, non-significant; *p > .05 modes (Liu et al, 2019). Therefore, PM_CBP, which harbours a CDA- We found that interference with PM_CBP expression reduces the thickness of the Ixodes PM and impacts its integrity, thereby increasing its permeability to large molecules.…”
Section: Discussionmentioning
confidence: 79%
“…In silico analyses have indicated that PM_CBP has a putative domain that belongs to the carbohydrate esterase 4 (CE4) superfamily, which includes the CDA proteins that catalyse the hydrolysis of acetyl groups from chitin to chitosan (Dixit et al, 2008; Luschnig, Batz, Armbruster, & Krasnow, 2006; Tsigos, Martinou, Kafetzopoulos, & Bouriotis, 2000). The crystal structures of several CDAs are available, including ones from insects, which together imply the conservation of critical residues in the active site (Liu et al, 2019), although extensive variations among these enzymes in the shapes of their substrate‐binding sites could lead to disparate substrate preferences and deacetylation modes (Liu et al, 2019). Therefore, PM_CBP, which harbours a CDA‐like domain, is expected to perform roles in the modification of PM structure and organisation, although its precise function remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike midgut CDAs, the deacetylation activity of BmCDA1 was detectable only when the cuticular chitin-binding protein CPAP-3A1 was added. 33) Taken together, the mechanism of insect CDAs to exhibit deacetylation activity was complexed and varied.…”
Section: Deacetylase Activitymentioning
confidence: 99%
“…( Figure 2 ) [ 26 ]. Crystal structures of several fungal CDAs suggest that their substrate binding site comprises four subsites, ranging from {−2} to {+1} [ 20 , 28 , 29 ], while some bacterial CDAs appear to have less subsites [ 29 ], and one insect CDA has been shown to possess a larger number of subsites [ 30 ].…”
Section: Regio-selective Chitin De- N -Acteylasmentioning
confidence: 99%